2018
DOI: 10.1016/j.ajhg.2018.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous Mutations in WEE2 Cause Fertilization Failure and Female Infertility

Abstract: Fertilization is a fundamental process of development and is a prerequisite for successful human reproduction. In mice, although several receptor proteins have been shown to play important roles in the process of fertilization, only three genes have been shown to cause fertilization failure and infertility when deleted in vivo. In clinical practice, some infertility case subjects suffer from recurrent failure of in vitro fertilization and intracytoplasmic sperm injection attempts due to fertilization failure, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
130
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 144 publications
(134 citation statements)
references
References 27 publications
4
130
0
Order By: Relevance
“…The locations and conservation analysis of mutant residues in WEE2. A, Distribution of mutations in WEE2 exons, mutations described in our previous study were marked in purple and novel mutations identified in this study were marked in green,mutations c.220_223 delAAAG and c.1006_1007insTA were both found in this study and our previous study. B, Location of mutations in the WEE2 protein, the green ball indicated novel mutations identified in this study, purple balls indicated mutation described in our previous study, p.E75Vfs*6 and p.H337Yfs*24 were both found in this study and our previous study.…”
Section: Resultssupporting
confidence: 65%
See 4 more Smart Citations
“…The locations and conservation analysis of mutant residues in WEE2. A, Distribution of mutations in WEE2 exons, mutations described in our previous study were marked in purple and novel mutations identified in this study were marked in green,mutations c.220_223 delAAAG and c.1006_1007insTA were both found in this study and our previous study. B, Location of mutations in the WEE2 protein, the green ball indicated novel mutations identified in this study, purple balls indicated mutation described in our previous study, p.E75Vfs*6 and p.H337Yfs*24 were both found in this study and our previous study.…”
Section: Resultssupporting
confidence: 65%
“…In the present study, we identified six affected individuals with nine mutations in WEE2 that are responsible for ICSI fertilization failure, among which mutation c.220_223 delAAAG (p.E75Vfs*6) and c.1006_1007insTA (p.H337Yfs*24) have been described in our previous study, the other seven are novel mutations. The function of WEE2 in the individuals from families 3, 4, and 5 was expected to be completely lost because of frameshift and nonsense mutations, and none of the retrieved oocytes from these patients could be fertilized.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations